1999
DOI: 10.1093/oxfordjournals.jbchem.a022426
|View full text |Cite
|
Sign up to set email alerts
|

A Cambialistic SOD in a Strictly Aerobic Hyperthermophilic Archaeon, Aeropyrum pernix

Abstract: The superoxide dismutase (SOD) gene of Aeropyrum pernix, a strictly aerobic hyperthermophilic archaeon, was cloned and expressed in Escherichia coli, and its gene product was characterized. The molecular mass of the protein, based on the deduced amino acid sequence, was 24.6 kDa. The sequence showed overall similarity to the sequences of known Mn- and Fe-SODs. The metal binding residues conserved in Mn- and Fe-SODs were also found in A. pernix SOD. When the SOD gene was expressed in E. coli cells, the product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 0 publications
3
39
0
Order By: Relevance
“…Both enzymes displayed relatively strong resistance against azide (Mnand Fe-SOD activity decreased 50% with 380 and 340 mM azide, respectively). This resistance against azide has also been observed in other archaeal SODs (44,45).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Both enzymes displayed relatively strong resistance against azide (Mnand Fe-SOD activity decreased 50% with 380 and 340 mM azide, respectively). This resistance against azide has also been observed in other archaeal SODs (44,45).…”
Section: Resultssupporting
confidence: 71%
“…However, it has previously been reported that SODs from Sulfolobus, although displaying similarly small molecular masses in gel filtration experiments (11,24), are actually composed of tightly packed tetramers (25,41). Since other SODs from hyperthermophilic archaea also exhibit the same tendency (42,45), this may also be the case for SOD Pc .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thermostable SODs are potentially very useful due to their high stability. It has been reported that SODs were isolated from hyperthermophilic organisms, [4][5][6][7][8][9][10] but reports about SODs from thermophilic fungi are few. The thermophilic fungus T. aurantiacus var.…”
mentioning
confidence: 99%
“…Therefore, a better understanding of the mechanism by which it protects itself against ROS would be of interest. A themostable superoxide dismutase was found in the genomic sequence of A. pernix and characterized (16). However, additional enzymes related to oxidative damage have not been reported.…”
mentioning
confidence: 99%